2021
DOI: 10.1111/jam.15152
|View full text |Cite
|
Sign up to set email alerts
|

Potential of root nodule nonrhizobial endophytic bacteria for growth promotion of Lotus corniculatus L. and Dactylis glomerata L.

Abstract: Aims: This research aimed to isolate and characterize nonrhizobial endophytic bacteria from root nodules of Medicago sativa L. and Lotus corniculatus L. with plant growth-promoting characteristics and to test its activity in a pot experiment with acid soil. Methods and Results: Out of 44 nonrhizobial isolates, the majority exhibited indole-3-acetic acid (IAA) production; 29 produced siderophores, few isolates performed phosphate solubilization and/or produced lytic enzymes, while 30% of isolates showed notable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In similar manner, Tapia-García et al [ 14 ] have studies 83 root nodule associated bacteria of which 56.6% were found to be IAA producers. In addition, Knežević et al [ 17 ] have reported 44 root nodule endophytic isolates from the root nodules of Medicago sativa L. and Lotus corniculatus L. and the majority exhibited indole-3-acetic acid (IAA) production. With regard to the quantity of synthesized IAA, the quantitified amounts of IAA produced were varied among the bacterial isolates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In similar manner, Tapia-García et al [ 14 ] have studies 83 root nodule associated bacteria of which 56.6% were found to be IAA producers. In addition, Knežević et al [ 17 ] have reported 44 root nodule endophytic isolates from the root nodules of Medicago sativa L. and Lotus corniculatus L. and the majority exhibited indole-3-acetic acid (IAA) production. With regard to the quantity of synthesized IAA, the quantitified amounts of IAA produced were varied among the bacterial isolates.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers also found that most of these passenger endophytes possessed plant growth promoting traits and further reported that the co-inoculation of two of these passenger endophytes with rhizobia significantly increased paba bean nodulation, growth and nitrogen uptake compared to single inoculated or un-inoculated treatments. Furthermore, Knežević et al [ 17 ] have reported 44 non-rhizobial isolates from the root nodules of nodules of Medicago sativa L. and Lotus corniculatus L. and revealed that the majority exhibited indole-3-acetic acid (IAA) production; 29 produced siderophores, few isolates performed phosphate solubilization and/or produced lytic enzymes, while 30% of isolates showed notable antifungal activity. The most promising strains were identified as members of Bacillus, Pseudomonas and Serratia genera, based on 16S rRNA sequence analysis in their study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their economic and ecological importance, relatively few studies (El-Batanony et al, 2020;Knežević et al, 2021;Das and Barik, 2022) have investigated the natural population of PGPR associated with the roots of L. corniculatus particularly in the Al-Ahsa region, which presents harsh conditions, such as drought, salinity, and elevated temperature. PGPR associated with the roots of L. corniculatus could reveal bacterial species that are previously unreported.…”
Section: Plant Growth-promoting Activitiesmentioning
confidence: 99%
“…L2Cr and LG from the Collection of the Institute of Soil Science were used for the inoculation or co-inoculation of soybean (variety Biser, maturity group 0). Pseudomonas strains were previously characterized and identified by Stajković et al (2009) and Knežević et al (2021). Pseudomonas strains were cultivated for 24 h in King B medium while Bradyrhizobium strains were grown in yeast mannitol broth (YMB) for 5 days.…”
Section: Soil and Experiments Designmentioning
confidence: 99%